The mining in the Amazon: A civilisational failure - Hallazi Méndez, Luis A. (2021)
Peru is, after Brazil, the country with the largest Amazonian territory. The disorganised occupation of this part of our territory shares responsibility with the government elites, since the disastrous decisions of those in power have resulted in an Amazon encircled by the ambitions of the extractivist model, one of these activities being mining. In this article we will see that any form of mining generates impacts on nature, the environment and people’s health. We will also show that in the Amazon, as it is an extremely fragile ecosystem, no type of mining should be carried out. An example of this is the situation in Madre de Dios due to illegal mining, which has devastated thousands of hectares of forest, contaminating rivers, lakes, fish and affecting the health of thousands of members of indigenous peoples.